Controversies in the Management of Life-Threatening Pulmonary Embolism - Marshall, Peter S.; Tapson, Victor; Jiménez, David (Seminars in Respiratory and Critical Care Medicine, 2015)
Patients with life-threatening pulmonary embolism (PE) offer clinicians a unique opportunity to intervene effectively on the patient's behalf. Hemodynamic status remains the most important short-term prognostic factor for patients with acute PE. Although the evidence is limited, the use of thrombolytic therapy is recommended for patients with acute symptomatic PE and associated hypotension or shock (i.e., high-risk PE) because these patients have a high short-term mortality risk (i.e., >15%) even when receiving anticoagulant treatment. In this setting, the hemodynamic benefits of thrombolytic treatment far outweigh its bleeding risk. For hemodynamically stable patients with PE, the identification of a subgroup of patients with a risk of PE-related complications similar to patients with PE and cardiovascular instability (i.e., intermediate-risk group) may assist with decision making regarding therapy. Given the lack of clear mortality benefit and increased bleeding risk, guidelines do not recommend routine use of systemic thrombolysis for this subgroup of patients. Careful monitoring and rescue fibrinolysis for intermediate-risk PE patients who experience hemodynamic compromise or deterioration while receiving standard anticoagulant therapy can minimize deaths from PE. For patients with life-threatening PE at high risk of bleeding, clinicians might consider the use of low-dose thrombolytic therapy, catheter-directed thrombolysis, or surgical embolectomy, if they have access to the required expertise and resources. The evidence does not support the use of inferior vena cava filters in patients with life-threatening PE unless there is a contraindication to anticoagulation. Since various medical and surgical specialties offer different perspectives and expertise, a multidisciplinary approach to patients with intermediate- and high-risk PE might improve patient outcomes.
Keywords: pulmonary embolism; survival; prognosis; risk stratification; thrombolysis; inferior vena cava filter